MODEL PENGEMBANGAN KOMPETENSI PEMASARAN PADA UKM DI PERKOTAAN - Arifin, Zainul (FIA UB, 2007)
Marketing competency is important factor for the manager of small business success. Small business in urban area faced various problems to survive their live and their business sustainability. This research was intended to identify the factors influencing marketing competency among managers of small business in urban area, especially at Malang City. Survey and interview technique were implemented among 32 small business managers in Malang City, started April 2007 until July 2007. Data was analyzed by using correlation and descriptive statistics. This research showed that individual quality and supporting business quality need improvement. Furthermore, a number of managers have a medium level of marketing competency, including their cognitive, affective and psycomotoric aspects. The marketing competencies were influenced by individual quality and supporting business quality. It was recommended that the purposes of promoting small business in urban area and the quality of life of managers, learning program that were developed based upon the competency and small business manager problems were required